Feedback regulation of apical progenitor fate by immature neurons through Wnt7–Celsr3–Fzd3 signalling - Wei Wang; Yves Jossin; Guoliang Chai; Wen-Hui Lien; Fadel Tissir; Andre M. Goffinet (Nature Communications, 2016)
The switch from neurogenesis to gliogenesis in cortical development is only partially understood. Here the authors show that Wnt-Planar cell polarity signaling in immature cortical neurons activates Notch in neural progenitor cells, thereby tuning the timing of their fate decisions.